2020
DOI: 10.1109/access.2020.3001130
|View full text |Cite
|
Sign up to set email alerts
|

A Reinforcement Learning-Based Framework for Robot Manipulation Skill Acquisition

Abstract: This paper studies robot manipulation skill acquisition based on a proposed reinforcement learning framework. Robot can learn policy autonomously by interacting with environment with a better learning efficiency. Aiming at the manipulator operation task, a reward function design method based on objects configuration matching (OCM) is proposed. It is simple and suitable for most Pick and Place skills learning. Integrating robot and object state, high-level action set and the designed reward function, the Markov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 39 publications
0
10
0
2
Order By: Relevance
“…Gualtieri et al [16] studied a method for learning Manipulation Skills through Hierarchical Spatial Attention to deal with the difficulty of learning a good attention policy and the added partial observability induced by a narrowed window of focus. Liu et al [17] proposed a reinforcement learning based framework for robot manipulation skill acquisition. Errante et al [18] reviewed and concluded that studies on cortical and subcortical circuits involved in grasping and manipulation might be promising to provide new insights about motor learning and brain plasticity in patients with motor disorders.…”
Section: Related Workmentioning
confidence: 99%
“…Gualtieri et al [16] studied a method for learning Manipulation Skills through Hierarchical Spatial Attention to deal with the difficulty of learning a good attention policy and the added partial observability induced by a narrowed window of focus. Liu et al [17] proposed a reinforcement learning based framework for robot manipulation skill acquisition. Errante et al [18] reviewed and concluded that studies on cortical and subcortical circuits involved in grasping and manipulation might be promising to provide new insights about motor learning and brain plasticity in patients with motor disorders.…”
Section: Related Workmentioning
confidence: 99%
“…Liu et al [66] designed a system to complete several robotic pick-and-place tasks, including stacking, sorting, and pin-in-hole placement. A major contribution of this paper was the work around reward shaping to solve complex problems.…”
Section: State Of Research-complete Pick-and-place Taskmentioning
confidence: 99%
“…Many approaches on the prediction of physical interactions have been applied from video prediction [15] to robotic manipulation tasks [16]. Some methods build the system dynamics by explicitly modeling the state transitions, leveraging ground-truth poses [17], [18] or known physical properties [19]. However, access to the ground-truth states and physical properties may be difficult for most real-world applications.…”
Section: Related Workmentioning
confidence: 99%